A supplementary report of the Pleistocene bovids from the Pabbi Hills of Pakistan. Issue 1 (3rd November 2021) - Dar, Fatima Yousuf; Aftab, Kiran; Abbas, Sayyed Ghyour; Babar, Muhammad Adeeb; Asim, Muhammad; Khan, Muhammad Akbar; Akhtar, Muhammad
Abstract : The Pleistocene mammalian remains of the Siwalik Group in Pakistan are less described than that of the Siwalik Miocene age. The recent expedition in the Pabbi Hills of Kharian has produced large mammalian remains, predominantly bovids forms. Proamphibos kashmiricus, Kobus sp., Hemibos triquetricornis, and Boselaphus namadicus have been described in this article, based on the new collection. The fourth upper deciduous premolar of B. namadicus is reported for the first time from the Pleistocene of the Siwalik Group. These taxa are large sized and found in the Pleistocene deposits of Pakistan. A Pleistocene savannah‐like landscape is suggested for these two localities. Abstract : The fossils are important because most of them represent the ancestors of the living asiatic fauna.